New replacement name for Angustella Li, 1986 (Hemiptera: Cicadellidae: Evacanthinae: Evacanthini), with description of a new species - Xing, Ji-Chun; Li, Zi-Zhong (Zootaxa, 2013)
A new replacement name Angustuma nom. nov. is proposed for the leafhopper genus Angustella Li, 1986 of the subfamily Evacanthinae (Hemiptera: Cicadellidae), and twelve new combinations are proposed. A new species Angustuma rudorsuma sp. nov. is described and illustrated from China. A key is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).